Production of biosurfactant from Candida cruzi isolated from produce water oil fields in Basrah for microbial enhance oil recovery - Al-Tamimi, Wijdan H.; Burghal, Ahmed A.; Abu-Mejdad, Najwa M. J. A. (Journal of Petroleum Research and Studies, 2018)
The produced water of Nahran Omar oil fields used for isolated the biosurfactant produce Candida cruzi which enhanced by using carbon and nitrogen sources, the biosurfactant production was followed by measuring the oil spreading, emulsification activity, oil collapse and cleaning oil contaminated vessels. The crud biosurfactant was able to spreading the oil (24) mm with (8%) emulsification activity and oil collapse of (++) the result of cleaning oil contaminated vessels revealed the recovered of oil from the wells of vessels. Under optimization of carbon and nitrogen sources the results revealed that the largest oil displacement was (9) mm with dextrin the maximum emulsification power was ( 92.8% and 92.5% ) for lactose and fructose respectively, these results demonstrated the high potential of emulsifiers produced by C. cruzi that can play an important role in application in enhance oil recovery